[Translated article] Knee osteoarthritis associated with extra-articular deformity treated by total knee arthroplasty plus simultaneous corrective osteotomy - L. Arbeloa-Gutierrez; A. Arenas-Miquelez; J. de Pablos (Revista Española de Cirugía Ortopédica y Traumatología, 2025)
Background and objective: Correct mechanical limb alignment is crucial in total knee arthroplasty (TKA) and is particularly difficult to achieve when the knee osteoarthritis (KOA) is associated with an extra-articular deformity (EAD). Our objective is to present a surgical option in cases of severe knee arthritis associated with an EAD (indications, mechanical planning and surgical technique), pros and cons and discuss the results with this one-stage technique. Material and methods: We retrospectively reviewed all cases of severe KOA associated with EAD treated surgically in our institution from 2010 to 2016. In our study, we only included cases treated via simultaneous TKA and corrective osteotomy (CO) and with a minimum follow-up period of three years. In terms of imaging, we determined the apex and angulation of the EAD as well as the modification of the mechanical parameters post-treatment. The pre- and postoperative clinical assessment was performed using the Knee Society Score (KSS). Results: Ten patients (10 knees) underwent combined surgery (simultaneous TKA and CO). The mean age was 67.7 years and the mean follow-up period was 49.2 months. The mechanical parameters were consistently corrected in the post-operative period. The mechanical axis deviation (MAD) shifted from a mean value of 6.9 cm to 0.45 cm and the joint line was rendered horizontal in all cases. In none of the cases did the bone resection affect the insertion of the collateral ligaments. The mean KSS value improved from 32.3 points preoperatively to 79.4 postoperatively. There were no major complications, but there were two planning errors that did not impact upon the end result. Conclusions: In severe associated KOA and EAD, the combined surgical treatment proposed achieves in one stage an effective anatomical and mechanical correction which is crucial to optimise clinical results and implant durability. The surgery is complex and requires careful planning. Resumen: Antecedentes y objetivo: La correcta alineación mecánica del miembro es crucial en la artroplastia total de rodilla (ATR), y es particularmente difícil de conseguir cuando a la artrosis de rodilla (AR) se asocia una deformidad extraarticular (DEA). Nuestro objetivo es mostrar esta opción quirúrgica en casos de artrosis severa de rodilla asociada a una DEA (indicaciones, planificación mecánica y técnica quirúrgica), sus pros y contras y discutir los resultados obtenidos empleando esta técnica en un solo tiempo quirúrgico. Material y métodos: Se revisaron retrospectivamente todos los casos de AR severa asociada a DEA operados entre 2010-2016 en nuestro centro. En el estudio se incluyeron solo los casos tratados mediante ATR y osteotomía correctora (OC) simultáneas y con seguimiento mínimo de 3 años. Radiológicamente se han determinado el ápex y la angulación de la DEA, así como la modificación de los parámetros mecánicos tras el tratamiento. La valoración clínica pre y postoperatoria se realizó mediante la escala Knee Society Score (KSS). Resultados: En 10 pacientes (10 rodillas) se realizó cirugía combinada (ATR + OC simultáneas). La edad media fue de 67,7 años y el seguimiento medio fue de 49,2 meses. Los parámetros mecánicos se corrigieron consistentemente en el postoperatorio. La desviación del eje mecánico (MAD) pasó de 6,9 cm a 0,45 cm de media y la línea articular quedó horizontal en todos los casos. En ningún caso la resección ósea invadió la inserción de los ligamentos colaterales. El valor medio del KSS mejoró de 32,3 puntos preoperatorios a 79,4 postoperatorios. No se produjeron complicaciones mayores, pero hubo dos errores de planificación sin influencia en el resultado final. Conclusiones: En AR y DEA severas asociadas el tratamiento quirúrgico combinado propuesto consigue, mediante un único procedimiento, una corrección anatómica y mecánica eficaces, lo que es crucial para optimizar los resultados clínicos y la durabilidad del implante. La cirugía es compleja, por lo que requiere una cuidadosa planificación.